Autonomous bed‐sediment imaging‐systems for revealing temporal variability of grain size. (24th June 2014) - Buscombe, Daniel; Rubin, David M.; Lacy, Jessica R.; Storlazzi, Curt D.; Hatcher, Gerald; Chezar, Henry; Wyland, Robert; Sherwood, Christopher R.
<x xml:space="preserve">Abstract</x> We describe a remotely operated video microscope system, designed to provide high‐resolution images of seabed sediments. Two versions were developed, which differ in how they raise the camera from the seabed. The first used hydraulics and the second used the energy associated with wave orbital motion. Images were analyzed using automated frequency‐domain methods, which following a rigorous partially supervised quality control procedure, yielded estimates to within 20% of the true size as determined by on‐screen manual measurements of grains. Long‐term grain‐size variability at a sandy inner shelf site offshore of Santa Cruz, California, USA, was investigated using the hydraulic system. Eighteen months of high frequency (min to h), high‐resolution (µm) images were collected, and grain size distributions compiled. The data constitutes the longest known high‐frequency record of seabed‐grain size at this sample frequency, at any location. Short‐term grain‐size variability of sand in an energetic surf zone at Praa Sands, Cornwall, UK was investigated using the 'wave‐powered' system. The data are the first high‐frequency record of grain size at a single location of a highly mobile and evolving bed in a natural surf zone. Using this technology, it is now possible to measure bed‐sediment‐grain size at a time‐scale comparable with flow conditions. Results suggest models of sediment transport at sandy, wave‐dominated, nearshore locations should allow for substantial changes in grain‐size distribution over time‐scales as short as a few hours.